Study of CNT Intercalated Bi2O3/PVDF Composite for Super Capacitors Applications. Issue 1 (20th October 2021) - Yadav, Dinesh Kumar; Yadav, Anju; Meena, Khushbu; Devat, Kiran; Mishra, Jitendra K.; Sahu, Rajesh; Jain, Sushil K.; Dixit, Ambesh; Srivastava, Nisha; Patodia, Tarun; Jakhar, Narendra; Tripathi, Balram
Abstract: Carbon nanotube (CNT) intercalated‐bismuth oxide (CNT‐Bi2 O3 )/polyvinylidenefluoride (PVDF) composites are synthesized via sonication and roasting process. The phase structure, bonding, and morphology of CNT‐Bi2 O3 /PVDF composite are characterized using X‐ray diffraction (XRD), Fourier transform infrared spectrum (FTIR), and scanning electron microscopy (SEM). The capacitance and dielectric constant of the composite electrodes are studied by impedance analyzer. The capacitance and stability of CNT‐Bi2 O3 /PVDF composite are found to be increased on increasing concentration of Bi2 O3 in PVDF composite. These results show that CNT‐Bi2 O3 /PVDF composite is a very promising electrode material for high‐performance super capacitors.